Saline pasture improve meat quality in Qinghai Tibetan sheep through changes in the rumen microbiota - Jia, Yujiao; Han, Lijuan; Hou, Shengzhen; Gui, Linsheng; Yuan, Zhenzhen; Sun, Shengnan; Wang, Zhiyou; Yang, Baochun; Yang, Chao (Frontiers in Microbiology, 2025)
IntroductionThis study aimed to investigate the effects of natural forage from different regions (saline-alkali and non-saline-alkali areas) on the rumen microbiota, muscle metabolites, and meat quality of Tibetan sheep.MethodsTargeted and non-targeted metabolomics were used to comprehensively analyze both pasture and meat quality, metabolites. Additionally, 16S rDNA sequencing was employed to analyze the rumen microbial community structure of Tibetan sheep.ResultsThe results showed that the natural saline-alkali forage (HG group) had higher protein content, lower fiber content, higher relative feed value, and better quality. Metabolomic analysis revealed significant accumulation of flavonoids and upregulation of amino acid metabolism in the HG group. Additionally, the natural saline-alkali forage significantly increased amino acid deposition in Tibetan sheep muscle, markedly enhanced the redness value (a*), and significantly reduced the yellowness value (b*). Furthermore, the natural saline-alkali forage altered the rumen fermentation patterns in Tibetan sheep, leading to a significant increase in the abundance of F082 and WCHB1-41, while significantly reducing the abundance of Prevotellaceae_UCG-003. Correlation analysis revealed that these microbial taxa were significantly influenced by the natural saline-alkali forage,while also showing significant associations with muscle quality parameters (a*, b*) and metabolites (cysteine, C18:1n9, etc.).DiscussionOverall, the natural saline-alkali forage demonstrated superior quality and metabolite content compared to natural non-saline-alkali forage. Furthermore, this saline-alkali forage significantly influenced the abundance of specific rumen microbiota in Tibetan sheep, consequently regulating muscle coloration and amino acid deposition.